(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Hilmi E, Sari LK, Cahyo NT, Mahdiana A, Soedibja PHT, Sudiana E. 2021. Survival and growth rates of mangroves planted in vertical and horizontal aquaponic systems in North Jakarta, Indonesia. Biodiversitas 23: 687-694. Mangrove rehabilitation is aimed to reverse mangrove deforestation and degradation. Various efforts have been conducted to rehabilitate the degraded mangroves, yet problems arise when planting mangroves in the high and permanently water-logged areas in coastline. The aquaponic system is a mangrove planting method introduced to reduce the impact of permanent and high water inundation. This research aims to analyze the survival rate of mangroves planted using vertical and horizontal aquaponic systems in Jakarta’s north coast and investigate the correlation between physico-chemical environmental parameters and the survival and growth rates of the planted mangroves. The results showed that the survival rate of mangroves planted in the vertical aquaponic system reached 55.4-96.9%. On the other hand, the highest survival rate in the horizontal aquaponic system was obtained in mangrove planting at 80-100 cm from the bottom with survived plants between 70-90%. The height growth rate of mangroves planted in the aquaponic system was between 0.95-2.33 cm/month. The correlation analysis showed that soil salinity, soil pH and water salinity had a high correlation to support living trees of mangrove seedlings. Rhizophora apiculata, Rhizophora mucronata, and Rhizophora stylosa had highest survival and adaptation in this planting system.